Localized ideographs in education rhetoric: Polly Williams and a justice-driven ideology of choice. Issue 3 (3rd July 2021) - Jensen, Kelly
ABSTRACT: The Milwaukee Parental Choice Program (MPCP) is considered the nation's first private school voucher program and a landmark policy for the contemporary school choice movement. Less well-known is the policy actor responsible for its inception and her view of the policy as a means toward justice for a historically oppressed community. I analyze the discourse of Wisconsin State Representative Polly Williams within the historical context surrounding the MPCP's 1989 passage, arguing that Williams employs the ideograph "choice" to represent a justice-driven ideology distinct from the "choice" consumer logics of neoliberalism. To attend to the non-dominant ideologies associated with ideographs, this essay suggests that we more fully consider contestation, local geographies, rhetor positionality, and community resources in our ideographic analysis. This project recovers Williams's "choice" discourse to demonstrate the ways that "choice" can take on an alternative meaning for local publics. In doing so, I consider how the unequal circulation of non-dominant ideologies risks co-optation by more dominant ideologies.